Spatial distribution and influencing factors analysis of Hainan's tropical marine cultural landscape - Dong, Ruiyun; Li, Yang; Yang, Dinghai (SPIE, 2024)
This paper takes 155 tropical marine cultural landscapes in Hainan as the research subject. It employs methods such as Average Nearest Neighbor Index, Kernel Density Estimation, and Geographical Detectors, and utilizes the ArcGIS 10.8 software to analyze the spatial distribution characteristics and development influencing factors of Hainan's tropical marine cultural landscape. The results show that: 1. The tropical marine cultural landscapes in Hainan exhibit a clustered spatial distribution within the province. 2. The tropical marine cultural landscapes are relatively concentrated at the city and county scale, revealing an imbalanced distribution across various cities and counties in Hainan. 3. According to the Kernel Density Estimation results, the spatial distribution of Hainan's tropical marine cultural landscape is summarized as having Haikou and Sanya as the "dual cores," with Lingshui, Qionghai, Wanning, Wenchang, Danzhou, and Dongfang forming the "Eastern and Western belts," thereby exhibiting a "two cores and two belts" spatial characteristic. 4. The main factors influencing the development of the tropical marine cultural landscape are the density of graded roads, total tourism revenue, the GDP of the tertiary industry, and the number of tourist arrivals. Enhancing the accessibility and convenience of transportation, and the high-quality development of the tourism industry, can effectively promote the rapid development of the tropical marine cultural landscape.